Impact of mergers and acquisitions on firms’ performance adjusted to business cycle fluctuations in China - Yi Zhang; Tong Lin; Yuanbo Qiao (PLoS ONE, 2025)
This research mainly explored the effects of mergers and acquisitions (M&As) on the financial performance of Chinese listed companies and the determinants of post-M&A financial performance of mergers by incorporating adjustments for business cycle fluctuations. The research was divided into two parts. The first part applied data envelopment analysis (DEA) models for the calculation of the financial performance scores of mergers and non-mergers in six major sectors before and after M&As. Comparative analyses of financial performance trends between mergers and non-mergers in similar sectors revealed that M&As often decrease financial performance scores of mergers compared with non-mergers. The second part adopted regression analyses and robustness test to evaluate the effects of listing duration, financial leverage level, free cash flow and target type on post-M&A financial performance. The results showed that mergers’ sufficient listing duration, high financial leverages, adequate free cash flow and asset as target had significant positive impact on the post-M&A performance of mergers. Opposite to the free cash flow hypothesis, this study revealed that free cash flow is beneficial for mergers in China. These findings emphasized that lack of experience and managerial hubris are the primary factors contributing to the underperformance observed within the Chinese M&A market.